1972
DOI: 10.1037/h0032321
|View full text |Cite
|
Sign up to set email alerts
|

Help seeking, self-esteem, and achievement motivation: An attributional analysis.

Abstract: An experimental investigation of determinants of whether people in need will seek help from an available source was based on an attributional analysis of when seeking help is experienced as threatening to self-esteem. Subjects perceived that they were performing poorly on a social judgment task and that available guidelines could help them. Help was sought significantly more (a) when it was reasonable to attribute responsiblity for failure externally rather than to the self; (6) when the attributes linked to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
120
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(130 citation statements)
references
References 8 publications
10
120
0
Order By: Relevance
“…However, our analysis based on actual help-seeking behavior revealed the opposite pattern, as those with lower self-efficacy scores agreed to seek help, while those with higher self-efficacy scores refused to do so. In line both with previous research (e.g., Puustinen & Winnykamen, 1998) and with the consistency hypothesis (Tessler & Schwartz, 1972), these results not only indicate that self-efficacy may be the motivational factor that contributes to different help-seeking behaviors and to self-regulation in general (Moos & Azevedo, 2009) but also further emphasize the importance of behavioral measures in the field of help seeking.…”
Section: To Seek or Not To Seek Help?supporting
confidence: 78%
See 3 more Smart Citations
“…However, our analysis based on actual help-seeking behavior revealed the opposite pattern, as those with lower self-efficacy scores agreed to seek help, while those with higher self-efficacy scores refused to do so. In line both with previous research (e.g., Puustinen & Winnykamen, 1998) and with the consistency hypothesis (Tessler & Schwartz, 1972), these results not only indicate that self-efficacy may be the motivational factor that contributes to different help-seeking behaviors and to self-regulation in general (Moos & Azevedo, 2009) but also further emphasize the importance of behavioral measures in the field of help seeking.…”
Section: To Seek or Not To Seek Help?supporting
confidence: 78%
“…An analysis of the role of self-efficacy in help seeking based on help-seeking intentions would have led to the conclusion that the lower the students' self-efficacy, the more they tend to avoid seeking help as predicted according to the vulnerability hypothesis (Tessler & Schwartz, 1972). However, our analysis based on actual help-seeking behavior revealed the opposite pattern, as those with lower self-efficacy scores agreed to seek help, while those with higher self-efficacy scores refused to do so.…”
Section: To Seek or Not To Seek Help?mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that people are more likely to seek help when they believe that the problem they are experiencing is normative (i.e., many other people experience it; Nadler, 1990). Similarly, when a task is perceived as ego-central (as a quality that is central to one's self-esteem, e.g., a test of intelligence), people seek help less often than when the same task is perceived as task oriented (e.g., completing a puzzle as a game; Butler & Neuman, 1995;Tessler & Schwartz, 1972).…”
Section: Gender Roles and Perceptions Of Problems In Livingmentioning
confidence: 99%